Evaluating the Safety and Efficacy of Mental Health Apps for Patients on Waiting Lists - Rajaram, Anushka; Natheeswaran, Runisan; Lo, Margret; Saliba, Joseph (Prepared by the McMaster Research Shop for the Suicide Prevention Community Council of Hamilton, 2024)
This report has been prepared by Research Associates from the McMaster Research Shop at the request of the Suicide Prevention Community Council of Hamilton (SPCCH). The SPCCH is exploring interventions to support those in acute mental health crises often on long waiting lists for mental health treatment. They see the potential for mental health apps on smartphones to provide accessible and effective support, but it's unclear which smartphone apps (if any) are considered safe and effective, as judged by mental health professionals. As such, this research intended to evaluate existing (and prominent) mental health apps to propose a shortlist of apps to patients at risk of suicide waiting to be seen clinically. This report draws on academic and grey literature about existing mental health apps and evaluative frameworks from largely Canadian and American contexts to offer an evidence-based starting point for app evaluation. It also draws on the clinical expertise of two key informants to support the development of evaluation criteria and an overall understanding of both the opportunities and challenges for mental health apps in the treatment and management of diverse mental health concerns.
Keywords: Hamilton, community-engaged research, mental health, suicide prevention, e-mental health, e-health, mental health apps